We will discuss here about the method of finding the equation of a straight line in the two point form.
To find the equation of a straight line in the two point form,
Let AB be a line passing through two points A (x\(_{1}\), y\(_{1}\)) and B (x\(_{2}\), y\(_{2}\)).
Let the equation of the line be y = mx + c ................... (i), where m is the slope of the line and c is the yintercept.
As (x\(_{1}\), y\(_{1}\)) and (x\(_{2}\), y\(_{2}\)) are points on the line AB, (x\(_{1}\), y\(_{1}\)) and (x\(_{2}\), y\(_{2}\)) satisfy (i).
Therefore, y\(_{1}\) = mx\(_{1}\) + c ................................ (ii)
and y\(_{2}\) = mx\(_{2}\) + c ................................ (iii)
Subtracting (iii) from (ii),
y\(_{1}\)  y\(_{2}\) = m(x\(_{1}\)  x\(_{2}\))
⟹ m = \(\frac{y_{1}  y_{2}}{x_{1}  x_{2}}\) ................................ (iv)
Substituting m = \(\frac{y_{1}  y_{2}}{x_{1}  x_{2}}\) in (ii),
y\(_{1}\) = [\(\frac{y_{1}  y_{2}}{x_{1}  x_{2}}\)]x\(_{1}\) + c
⟹ c = y\(_{1}\)  \(\frac{x_{1}(y_{1}  y_{2})}{ x_{1}  x_{2}}\)
⟹ c = \(\frac{ y_{1}(x_{1}  x_{2})  x_{1}(y_{1}  y_{2})}{ x_{1}  x_{2}}\)
⟹ c = \(\frac{x_{1}y_{2}  x_{2}y_{1}}{ x_{1}  x_{2}}\)
Therefore, from (i),
y = [\(\frac{y_{1}  y_{2}}{x_{1}  x_{2}}\)]x + \(\frac{x_{1}y_{2}  x_{2}y_{1}}{ x_{1}  x_{2}}\)
Subtracting y\(_{1}\) from both sides of (v)
y  y\(_{1}\) = [\(\frac{y_{1}  y_{2}}{x_{1}  x_{2}}\)]x + \(\frac{x_{1}y_{2}  x_{2}y_{1}}{ x_{1}  x_{2}}\)
⟹ y  y\(_{1}\) = [\(\frac{y_{1}  y_{2}}{x_{1}  x_{2}}\)]x + \(\frac{x_{1}(y_{2}  y_{1})}{ x_{1}  x_{2}}\)
⟹ y  y\(_{1}\) = \(\frac{y_{1}  y_{2}}{x_{1}  x_{2}}\)(x + x\(_{1}\))
The equation of the straight line passing through (x1, y1) and (x2, y2) is y  y\(_{1}\) = \(\frac{y_{1}  y_{2}}{x_{1}  x_{2}}\)(x + x\(_{1}\))
Note: From (iv), the slope of the line joining the points (x\(_{1}\), y\(_{1}\)) and (x\(_{2}\), y\(_{2}\)) is \(\frac{y_{1}  y_{2}}{x_{1}  x_{2}}\) i.e., \(\frac{Difference of ycoordinates}{difference of xcoordinates in the same order}\)
Solved example on twopoint form of a line:
The equation of the line passing through the points (1, 1) and (3, 2) is
y  1 = \(\frac{1  2}{1  (3)}\)(x  1)
⟹ y – 1 = \(\frac{1}{4}\)(x – 1)
Also, y – 2 = \(\frac{2  1}{3  1}\)(x + 3)
⟹ y – 2 = \(\frac{1}{4}\)(x + 3)
However, the two equations are the same.
`● Equation of a Straight Line
From Pointslope Form of a Line to HOME
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.

New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.